RUU PERTANAHAN: ANTARA MANDAT DAN PENGINGKARAN TERHADAP UUPA 1960 - Gunawan, Gunawan (BHUMI: Jurnal Agraria dan Pertanahan, 2018)
The sense of agrarian term covers the surface of the earth (land ). The land law ought to refer to the agrarian law. The planning of land constitution should also refer to the Constitution No. 5, 1960 on Basic Agrarian Law. Whether the planning of land constitution opposes the Basic Agrarian Law can be verified by the question on how far the above planning is made. This was mandated by the Basic Agrarian Law. Keywords: land law, right on land, land jurisdiction